2001
DOI: 10.2337/diabetes.50.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Role of Bcl-2 in Rat Blastocysts Exposed to High D-Glucose

Abstract: Bcl-2 mRNA expression was detected in rat blastocysts by in situ hybridization. The distribution of mRNA expression was rather heterogenous, with ~2% of highexpressing cells. In vitro exposure to 28 mmol/l D-glucose for 24 h resulted in a significant increase in the proportion of these cells compared with control embryos in either 6 mmol/l D-glucose or 28 mmol/l D+L-glucose. Heterogeneity in the expression of Bcl-2 was also observed at the protein level by immunocytochemistry. Exposure to 28 mmol/l D-glucose s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 28 publications
1
15
2
Order By: Relevance
“…A recent report suggested that an acute physiological increase in plasma leptin levels inhibits glucose-stimulated insulin secretion [33]. However, these findings are in contrast with the observation of a decreased second-phase insulin secretion in response to free fatty acids in subjects with the less active form of the Pro12Ala variant [34]. A recent in vivo study showed that leptin synthesis was adipose tissue site-dependent on CCAAT/enhancer binding protein-α (C/EBPα) [35]which in turn modulates the transactivation of the PPARγ promoter [36], supporting the idea of a close regulatory paracrine mechanism.…”
Section: Discussioncontrasting
confidence: 55%
“…A recent report suggested that an acute physiological increase in plasma leptin levels inhibits glucose-stimulated insulin secretion [33]. However, these findings are in contrast with the observation of a decreased second-phase insulin secretion in response to free fatty acids in subjects with the less active form of the Pro12Ala variant [34]. A recent in vivo study showed that leptin synthesis was adipose tissue site-dependent on CCAAT/enhancer binding protein-α (C/EBPα) [35]which in turn modulates the transactivation of the PPARγ promoter [36], supporting the idea of a close regulatory paracrine mechanism.…”
Section: Discussioncontrasting
confidence: 55%
“…Bcl-2 and Bcl-X L act as apoptosis repressors, whereas Bax and Bad act as apoptosis promoters (Oltvai et al, 1993;Kroemer, 1997). Previous studies demonstrated that streptozotocin induces apoptosis through downregulation of Bcl-2 protein and the high glucose condition increases apoptosis in rat blastocysts by a decrease of Bcl-2 expression (Pampfer et al, 2001;Jesmin et al, 2006). This study demonstrated the change of Bcl-2 family proteins in the testis of diabetic animals.…”
Section: Discussionmentioning
confidence: 95%
“…[45][46][47][48][49][50] We suggest that apoptosis, in particular differential apoptosis of specific renal lineages during nephrogenesis, induced by a high-glucose milieu, is the major mechanism by which renal function is ultimately affected in diabetic offspring over time. The activation of intrarenal RAS and NF-B pathways are two key mechanisms that seem critical in the apoptosis induced by an intrauterine high-glucose milieu.…”
Section: Discussionmentioning
confidence: 99%